2016
DOI: 10.1101/040907
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Atomic structure of Hsp90:Cdc37:Cdk4 reveals Hsp90 regulates kinase via dramatic unfolding

Abstract: The Hsp90 molecular chaperone and its Cdc37 co-chaperone help stabilize and activate over half of the human kinome. However, neither the mechanism by which these chaperones assist their client kinases nor why some kinases are addicted to Hsp90 while closely related family members are independent is known. Missing has been any structural understanding of these interactions, with no full-length structures of human Hsp90, Cdc37 or either of these proteins with a kinase. Here we report a 3.9Å cryoEM structure of t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The modeled Hsp90␤ dimer structure (Fig. S6) was in complete agreement with its closed counterpart (30). Each of the four compounds (ATP, GA, NB, and KU-32) was docked, and their ⌬G of binding was calculated (Table S1).…”
Section: Hsp90 Adopts a Partially Closed Conformation Upon Ku-32 Bindingmentioning
confidence: 53%
“…The modeled Hsp90␤ dimer structure (Fig. S6) was in complete agreement with its closed counterpart (30). Each of the four compounds (ATP, GA, NB, and KU-32) was docked, and their ⌬G of binding was calculated (Table S1).…”
Section: Hsp90 Adopts a Partially Closed Conformation Upon Ku-32 Bindingmentioning
confidence: 53%
“…Two cryoelectron microscopy (cryo-EM) structures (Vaughan et al, 2006; Verba et al, 2016) have shown that kinase domains interact with Hsp90 in an extended conformation, indicating that they undergo a large-scale structural rearrangement when in complex with Hsp90. However, Hsp90 does not form stable complexes with either bRaf or Cdk4 (Polier et al., 2013; Vaughan et al, 2006), despite the fact that the corresponding stable ternary Hsp90-Cdc37-kinase complexes can be formed.…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible to assume that stable association of Cdk4 with Hsp90 occurs through a similar Cdc37-mediated conformational rearrangement of the kinase domain that involves partial unfolding. In this respect, the latest high-resolution cryo-EM structure of Hsp90-Cdc37-Cdk4 shows that the β 4 -β 5 strands and αC-β 4 loop of Cdk4 are completely unfolded, allowing the two kinase lobes to become separated (Verba et al, 2016). Notably, these structural elements partially overlap with the bRaf regions that expose unique proteolytic sites in complex with Cdc37 (Figures 4B and 4C; Supplemental Information) and, particularly, the αC-β4 loop and the beginning of β 4 strand.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a recent cryo-electron microscopy study of a complex between protein kinase Cdk4, the cochaperone Cdc37, and human Hsp90 showed that the beta 5 strand of the kinase client is clamped between the two opposed middle domains of the Hsp90 dimer in the client-chaperone complex. The Cdc37 in this complex is also wrapped around the M 1 domain [61]. Together these data point to the essential role of the M 1 domain in client protein maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, however, the grpN-hspMC chimera (4), which does not bind Cdc37 in our pulldown assay, nonetheless supports yeast viability. The Hsp90 binding site for Cdc37 was originally mapped to the N-terminal domain [42], but recent data from the cryo-EM structure of the Cdk4-Cdc37-hHsp90 complex [61] reveals that, in the context of the client assembly, Cdc37 makes the vast majority of its interactions with the M 1 domain of the chaperone ( Fig 7A ). Thus, although the grpN-hspMC chimera (4) lacks the cognate Hsp90 N-terminal domain, it does contain the alternate Hsp90 M 1 binding site for Cdc37 that is used in the context of client complexes.…”
Section: Discussionmentioning
confidence: 99%